2022
DOI: 10.3390/coatings12020176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxidation and Crystallization on Pitting Initiation Behavior of Fe-Based Amorphous Coatings

Abstract: Fe-based amorphous coatings are typically fabricated by high-velocity oxygen-fuel spraying using industrial raw materials. The bonding mode between the coating particles and the corrosion mechanism of the coating in the chloride-rich environment were studied. The results indicate that some fine crystallites such as α-Fe and Fe3C tend to precipitate from the amorphous matrix as the kerosene flow rate increases or the travel speed of spraying gun decreases. Moreover, some precipitates of the (Cr, Fe)2O3 nanocrys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Compared to the conventional plasma-sprayed (PS) and HVOF-sprayed coatings, it can be found that the low-pressure plasma-sprayed (LPPS) coating has a considerable advantage over the conventional spraying method in terms of forming, and the average hardness is also higher than that of the other two coatings, indicating excellent performance in Figure 9.
Figure 9 Properties of iron-based AMC with different spraying methods [18,23,24,28,31,4148].
…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the conventional plasma-sprayed (PS) and HVOF-sprayed coatings, it can be found that the low-pressure plasma-sprayed (LPPS) coating has a considerable advantage over the conventional spraying method in terms of forming, and the average hardness is also higher than that of the other two coatings, indicating excellent performance in Figure 9.
Figure 9 Properties of iron-based AMC with different spraying methods [18,23,24,28,31,4148].
…”
Section: Resultsmentioning
confidence: 99%
“…To obtain the metallic glass structure during spraying, special conditions must be created, namely, rapid heating of the particles to the molten state and a high cooling rate due to heat dissipation into the volume of the substrate material. During the spraying process, oxidation of the sprayed powder should be avoided, as the oxide lms formed on the surface favor heterogeneous nucleation, and negatively affect the properties of the coatings [17][18][19][20][21][22]. Among thermal spraying methods, the impulse nature of detonation spraying allows the formation of wear resistant and dense coatings with low crystalline phase content [23].…”
Section: Introductionmentioning
confidence: 99%